Exploring Themes, Narrative Progression And Character Development In Hoover’s It Ends With Us: A Pragmatic Analysis - Dr. Fatima Zafar Baig, Ayesha Waheed, Mashaal Aman (Migration Letters, 2024)
This study examines the impact of speech acts on character development, plot development, and thematic exploration in Hoover’s novel It Ends with Us. The research examines how these speech acts shape the narrative and deepen readers’ understanding of the characters’ internal and external conflicts by utilizing John Searle’s taxonomy of illocutionary acts—assertives, directives, commissives, expressives, and declarations. Commissives highlight promises and commitments central to character motivations, expressives reveal emotional depth, and declarations mark pivotal moments that alter the story’s reality. Assertive speech acts reveal characters’ beliefs; directives propel the plot through influencing actions. The study emphasizes the significance of expressive speech acts in reinforcing themes of love, resilience, and personal development and revealing the emotions of characters. This study contributes to literary linguistics by [1]demonstrating how speech acts function as essential tools for storytelling and meaning-making in contemporary literature by analyzing the nuanced interactions between language use and narrative construction. The results shed more light on how Hoover’s thematic exploration, narrative progression, and character dynamics are influenced by language.